The Effect of Implementing a Digital Payment System on Sales of the Kopma Business Unit “Alma mater” at Makassar State University - Amirul Amri; Zainal Ruma; Muhammad Ilham Wardhana Haeruddin; Burhanuddin; Muh. Ichwan Musa (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of implementing a digital payment system on sales at the Kopma Alma mater business unit, Makassar State University. The number of respondents in this study were 50 people. This type of research uses quantitative research with a non-probability sampling technique that does not provide equal opportunities for each element of the population to be selected as a sample. In the sense that the samples taken are consumers who use digital payments. The collection of data used is a questionnaire and documentation. The analytical method in this study uses instrument tests (validity test, reliability test), classic assumption test (normality test), coefficient of determination test, and t test. The results of the study show that the digital payment system has a positive and significant effect on sales at the Kopma Alma mater business unit, Makassar State University